2022
DOI: 10.1051/0004-6361/202141295
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the physics behind the non-thermal emission from star-forming galaxies detected in γ rays

Abstract: Context. Star-forming galaxies emit non-thermal radiation from radio to γ rays. Observations show that their radio and γ-ray luminosities scale with their star formation rates, supporting the hypothesis that non-thermal radiation is emitted by cosmic rays produced by their stellar populations. However, the nature of the main cosmic-ray transport processes that shape the emission in these galaxies is still poorly understood, especially at low star formation rates. Aims. Our aim is to investigate the main mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 120 publications
3
12
0
Order By: Relevance
“…It has, therefore, been suggested that starburst galaxies are CR calorimeters, i.e. the total gamma-ray and neutrino output from starburst galaxies may approach the total energy output in cosmic rays [248][249][250][251][252]. In fact, the expected diffuse neutrino emission associated with starburst galaxies is intriguingly close to observations by the IceCube observatory [250].…”
Section: Topicsupporting
confidence: 56%
“…It has, therefore, been suggested that starburst galaxies are CR calorimeters, i.e. the total gamma-ray and neutrino output from starburst galaxies may approach the total energy output in cosmic rays [248][249][250][251][252]. In fact, the expected diffuse neutrino emission associated with starburst galaxies is intriguingly close to observations by the IceCube observatory [250].…”
Section: Topicsupporting
confidence: 56%
“…This equation shows that scaling the energy-loss timescale by a factor of (Γ − 1) −1 gives a slightly more precise normalization for spectra with Γ = 2 than the simplest approximation that assumes f CR (p) = τ loss • Q CR (p) even though the qualitative results do not change, as already emphasized by Ref. [56]. Finally, we stress that it is important to calculate the CR transport equation into the momentum space, because from a theoretical point of view the CRs are injected with a momentum power-law spectrum [61,94], even though many authors simply assume a power-law spectrum in the energy space.…”
Section: The Leaky-box Model Approximationsupporting
confidence: 53%
“…For the dimension of the nuclei R SBN , we account for a variation of a factor 2 with respect to the value expected for SBN circumnuclear region [51,54,97,98]. The range for the wind velocity is fixed according to the recent analyses [51,54,56,93,99]. Finally, for the gas density n ISM , the two sources require different priors according to the empirical Kennicut relation [97,98,100].…”
Section: Linear Priors For the Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since core collapse SNe rapidly follow star formation, it is therefore natural to expect a linear relationship between star formation rate and CR injection into a galaxy, and thus at least potentially between star formation rate and non-thermal emission that traces CRs. The extent to which such a relationship holds, and to which particular galaxies deviate from it, can then be interpreted as constraining the fraction of CRs that escape ★ E-mail: mark.krumholz@anu.edu.au (MRK) from galaxies; this in turn can be used to illuminate the physics of CR transport through interstellar gas (e.g., Lacki et al 2011;Krumholz et al 2020;Ajello et al 2020;Kornecki et al 2020Kornecki et al , 2022Crocker et al 2021a;Werhahn et al 2021b,c;Ambrosone et al 2022). A crucial input to these interpretive efforts is the total 𝛾-ray production budget associated with star formation -i.e., in a galaxy that is perfectly calorimetric, such that all the CRs accelerated by young stars and their feedback give up their energy within the galaxy, what 𝛾-ray luminosity would we expect per unit mass of stars formed?…”
Section: Introductionmentioning
confidence: 99%